Patient-reported outcomes in CodeBreaK 200: sotorasib versus docetaxel for previously treated advanced NSCLC with KRAS G12C mutation - Waterhouse, David M.; Rothschild, Sacha; Dooms, Christophe; Mennecier, Bertrand; Bozorgmehr, Farastuk; Majem, Margarita; van den Heuvel, Michel H.; Linardou, Helena; Chul Cho, Byoung; Roberts-Thomson, Rachel; Tanaka, Kentaro; Blais, Normand; et al. (Lung cancer, 2024)
Background - In the CodeBreaK 200 phase III, open-label trial, sotorasib significantly improved efficacy versus docetaxel in previously treated KRAS G12C-mutated advanced non-small cell lung cancer (NSCLC). Patient-reported outcomes (PROs) for global health status, physical functioning, dyspnea, and cough favored sotorasib over docetaxel. Here, we report sotorasib’s additional impact on quality of life (QOL). - Methods - In CodeBreaK 200, 345 patients who had progressed after prior therapy received sotorasib (960mg orally daily) or docetaxel (75mg/m2 intravenously every 3weeks). Validated questionnaires captured patients’ perception of their QOL and symptom burden for key secondary and exploratory PRO endpoints, including the European Organisation for Research and Treatment of Cancer Quality-of-life Questionnaire Core 30 (EORTC QLQ-C30) and Quality-of-life Questionnaire Lung Cancer 13 (EORTC QLQ-LC13), question GP5 from the Functional Assessment of Cancer Therapy Tool General Form (FACT-G GP5), PRO-Common Terminology Criteria for Adverse Events (PRO-CTCAE), and 5-level EuroQOL-5 dimensions (EQ-5D-5L) including visual analog scale (EQ-5D VAS). Change from baseline to week 12 was assessed with generalized estimating equations for ordinal outcomes. - Results - Patients receiving sotorasib were less bothered by treatment side effects than those receiving docetaxel (odds ratio [OR] 5.7) and experienced symptoms at lower severity (pain: OR 2.9; aching muscles: OR 4.4; aching joints: OR 4.2; mouth or throat sores: OR 4.3). Further, patients’ symptoms interfered less with usual/daily activities (pain: OR 3.2; aching muscles: OR 3.9; aching joints: OR 10.7). QOL remained stable with sotorasib but worsened with docetaxel (change from baseline in EQ-5D VAS score: 1.5 vs -8.4 at cycle 1day 5 and 2.2 vs -5.8 at week 12). - Conclusions - Patients receiving sotorasib reported less severe symptoms than those receiving docetaxel. In addition to improving clinical efficacy outcomes, sotorasib maintained QOL versus docetaxel, suggesting sotorasib may be a more tolerable treatment option for patients with pretreated, KRAS G12C-mutated advanced NSCLC.